Pengaruh Permainan Tradisional Congklak terhadap Kemampuan Berhitung Anak Usia Dini - Nur Salsabila Amara; Mita Sari; Nurhalimawati Maruwa; Amelia Dunggio; Putri Lagia; Zahra Tusita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the effect of the traditional congklak game on early childhood numeracy skills at TK Beringin. The research employed a quantitative method with an experimental design using a One-Group Pretest-Posttest Design. The population consisted of all children at TK Beringin, totaling 30 children, including 10 boys and 20 girls. The sampling technique used was total sampling, meaning the entire population was included as the research sample. Data were collected through observation and numeracy skill tests administered before and after treatment using the traditional congklak game. Data analysis was conducted using the t-test to examine the effect of the treatment. The results showed an improvement in children’s numeracy skills after using the traditional congklak game, as indicated by the increase in the average pre-test score from 2.29 to a post-test score of 3.08, with a gain score of 0.78. The hypothesis test showed that the t-count value of 9.12 was greater than the t-table value of 2.045 at the 5% significance level. Thus, the traditional congklak game had a significant effect on improving early childhood numeracy skills.